Relationships between psychological empowerment with work motivation and withdrawal intention among secondary school principals in Malaysia - Chan, Yuen Fook; Britten, Linton @ Jerah; Sidhu, Gurnam Kaur; Foo, Say Fooi (Elsevier, 2011)
This study attempts to investigate factors that influence the psychological empowerment with work motivation and work withdrawal intention of school principals in Malaysia. The sample population comprised school principals. A total of 101 self-administered questionnaires were analysed. Pearson product moment correlation coefficients (Pearson r's) or Point bi-serial (rpb) coefficients were computed between the psychological empowerment total scores and those of the independent variables (or subvariables). Total scores from the four psychological empowerment dimensions and the PE-Overall were correlated individually with scores from the independent variables of Work Motivation and Work Withdrawal Intention. Results indicated all five aspects of psychological empowerment (PE-Overall, PE-Meaning, PE-Competence, PE-Self-determination and PE-Impact) correlated positively and significantly with the Intrinsic Work motivation domain. This study also proves that when withdrawal intentions increased, the dimensional component levels of psychological empowerment decreased correspondingly.